Relationships of native trees with grasses in a temperate, semi‐arid sandy ecosystem of northern China. Issue 2 (4th September 2013) - Yang, Hongxiao; Chu, Jianmin; Lu, Qi; Gao, Ting; Verheyen, Kris
Abstract Question Afforestation is a controversial method for restoring semi‐arid sandy ecosystems to control desertification. We studied how native elm trees (Ulmus pumila L.) interact with grasses in the semi‐arid sandy ecosystem of the Otindag, and how the trees should be arranged to promote ecological restoration. Location Otindag Sandy Land, Inner Mongolia, northern China. Methods Using 40 adult elms, we investigated and compared root depths of the native trees with those of neighbouring grasses. The shallowest elm roots and the deepest grass roots were analysed. Using four singleton elms, we also examined how soil moisture in the different soil layers (0–10, 10–20, 20–30 and 30–40 cm) and grass biomass density changed with distance from the corresponding tree trunks in four directions within 19 m. Results On average, the shallowest elm roots were 17.6 cm deep at 1 m from the elm trunks, and 24.5 cm at 3 m from the elm trunks, whereas the deepest grass roots were 14 cm deep at 1 m from the trunks, and 16.3 cm deep at 3 m from the trunks. The moisture content in the 0–20 cm layers decreased with distance from 1 to 19 m from the singleton elms, but increased along the same distance gradient in the 20–40 cm layers. Grass biomass density decreased along the distance gradient, and a logistic model fits this tendency well, which indicates that the grass biomass density levels off at distances of >ca. 9 m. Conclusions Given the vertical divergence of roots and the horizontal pattern of soil moisture, the adult native trees do not compete for much moisture with grasses. The adult native trees have the potential to facilitate the growth and biomass accumulation of nearby grasses. In the semi‐arid sandy ecosystem of the Otindag, native elms can be planted for ecological restoration at intervals of up to 18 m.